Main content

## 8th grade

### Unit 4: Lesson 3

Solving systems with substitution- Systems of equations with substitution: 2y=x+7 & x=y-4
- Systems of equations with substitution
- Systems of equations with substitution: y=4x-17.5 & y+2x=6.5
- Systems of equations with substitution: -3x-4y=-2 & y=2x-5
- Systems of equations with substitution: 9x+3y=15 & y-x=5
- Systems of equations with substitution
- Systems of equations with substitution: y=-5x+8 & 10x+2y=-2
- Systems of equations with substitution: y=-1/4x+100 & y=-1/4x+120
- Substitution method review (systems of equations)

© 2022 Khan AcademyTerms of usePrivacy PolicyCookie Notice

# Systems of equations with substitution: -3x-4y=-2 & y=2x-5

CCSS.Math: , ,

Learn to solve the system of equations -3x - 4y = -2 and y = 2x - 5 using substitution. Created by Sal Khan.

## Video transcript

So that it's less likely that we get shown up by talking birds in the future, we've set a little bit of exercise for solving systems of equations with substitution. And so this is the first exercise or the first problem that they give us. -3x-4y=-2 and y=2x-5 So let me get out my little scratch pad and let me rewrite the problem. So this is -3x-4y=-2 and then they tell us y=2x-5. So, what's neat about this is that they've already solved the second equation. They've already made it explicitly solved for y which makes it very easy to substitute for. We can take this constraint, the constraint on y in terms of x and substitute it for y in this first blue equation and then solve for x. So let's try it out. So this first blue equation would then become -3x-4 but instead of putting a y there the second constraint tells us that y needs to be equal to 2x-5. So it's 4(2x-5) and all of that is going to be equal to -2. So now we get just one equation with one unknown. and now we just have to solve for x. So, let's see if we can do that. So, it's -3x and then this part right over here we have a -4, be careful, we have a -4 we want to distribute. We are going to multiply -4*2x which is -8x and -4*-5 is positive 20 and thats going to equal -2. And now we can combine all the x terms so -3x-8x, that's going to be -11x and then we have -11x+20=-2. Now to solve for x, we'll subtract 20 from both sides to get rid of the 20 on the left hand side. On the left hand side, we're just left with the -11x and then on the right hand side we are left with -22. Now we can divide both sides by -11. And we are left with x is equal to 22 divided by 11 is 2, and the negatives cancel out. x = 2. So we are not quite done yet. We've done, I guess you can say the hard part, we have solved for x but now we have to solve for y. We could take this x value to either one of these equations and solve for y. But this second one has already explicitly solved for y so let's use that one, so it says y = 2 times and instead of x, we now know that the x value where these two intersect, you could view it that way is going to be equal to 2, so 2 * 2 - 5 let's figure out the corresponding y value. So you get y=2(2)-5 and y = 4 - 5 so y = -1. And you can verify that it'll work in this top equation If y = -1 and x=2, this top equation becomes -3(2) which is -6-4(-1) which would be plus 4. And -6+4 is indeed -2. So it satisfies both of these equations and now we can type it in to verify that we got it right, although, we know that we did, so x=2 and y=-1. So, let's type it in... x=2 and y=-1. Excellent, now we're much less likely to be embarassed by talking birds.